PENINGKATAN NILAI TAMBAH PRODUK PERIKANAN UNTUK PENINGKATAN EKONOMI MASYARAKAT PESISIR SULAWESI BARAT - Saputra, Eka; Andriyono, Sapto; Isroni, Wahyu (Jurnal Abdi Insani, 2024)
The problems faced by coastal communities are business expansion and empowerment of fisherwomen to process some of the catch into diversified food products. Processed fish products that are in demand by the community are a promising business opportunity, this requires technology to produce good products. Diversification is one form of effort to improve public health. This activity aims to increase fish consumption in the community and can also be used as a material for further products such as animal feed, especially related to waste from the fish processing process. This activity is divided into 3 stages, namely the first to collect aspirations and information. The second is solving problems that exist at the location and the third is evaluating activities. From the results of the activities that have been carried out, the results obtained are getting information on the types of fish that are popularly consumed by the community and fish that are rarely consumed by the surrounding community. Many people still do not know that fish can be used as raw materials to be made into diversified food products such as fish balls, fish nuggets, fish crackers and others. The results of these diversification products can be used by the community as one way to increase fish consumption for the community, especially for children who do not like fish because of the shape of the fish or the aroma and others. It can also be used as a means of educating the world of fisheries for both adults and children, so that later efforts to maintain the sustainability of fisheries can be improved. The conclusion of this activity is that the community gets information that fish can be used as a derivative product through diversification to increase fish consumption.